(untitled) (New York, 1993)
The vast range of environmental habitats inhabited by fish varies immensely, and the successful maintenance of fish populations in challenging environments requires responsive adjustments in physiology. Ecophysiology forms the interface between ecology and physiology, overlapping with other disciplines such as behaviour and morphology. "Fish Ecophysiology" describes how the physiology of fisheries is affected by and regulated in response to environmental changes. There is great concern, internationally, about the impact of man's activities on the environment, as well as the potential environmental changes which may be brought about by predicted global climate changes. A full understanding of the effects of environmental and potential habitat changes of fish physiology is vital to all those working in this area.
Keywords: Fishes,Adaptation (Physiology)